HiSStology: high spectral and spatial resolution magnetic resonance imaging detection of vasculature validated by histology and micro-computed tomography. - Haney, C; Pelizzari, C; Foxley, S; Zamora, M; Mustafi, D; Tretiakova, M; Li, S; Fan, X; Karczmar, G (2011)
High spectral and spatial resolution (HiSS) data, acquired with echo-planar spectroscopic imaging (EPSI), can be used to acquire water spectra from each small image voxel. These images are sensitive to changes in local susceptibility caused by superparamagnetic iron oxide particles (SPIO); therefore, we hypothesized that images derived from HiSS data are very sensitive to tumor neovasculature following injection of SPIO. Accurate image registration was used to validate HiSS detection of neovasculature with histology and micro-computed tomographic (microCT) angiography. Athymic nude mice and Copenhagen rats were inoculated with Dunning AT6.1 prostate tumor cells in the right hind limb. The tumor region was imaged pre- and post-intravenous injection of SPIO. Three-dimensional assemblies of the CD31-stained histologic slices of the mouse legs and the microCT images of the rat vascular casts were registered with EPSI. The average distance between HiSS-predicted regions of high vascular density on magnetic resonance imaging and CD31-stained regions on histology was 200 μm. Similarly, vessels identified by HiSS in the rat images coincided with vasculature in the registered microCT image. The data demonstrate a strong correlation between tumor vasculature identified using HiSS and two gold standards: histology and microCT angiography.